Accounting for the Cost of Interest. - Jaedicke, Robert K.; Anthony, Robert N. (Journal of Finance, 1976)
In economics, the word interest refers to the cost of using capital. The definition of interest in financial accounting differs from its economics definition in two fundamental respects. First, in financial accounting, interest refers only to the charge for using debt capital; accountants do not record a charge for the use of equity capital. Second, in financial accounting, interest is not ordinarily treated as an element of cost in the sense that labour and material are so treated; rather, interest on debt capital is regarded as an expense that is deducted in full from the revenues of the period in which the interest is incurred.